Gesetzliche Rente: bedeutet Teilhabeäquivalenz Verteilungsneutralität?ein weiterer Irrtum - Friedrich Breyer (Wirtschaftsdienst, 2013)
Ein Grundprinzip der Gesetzlichen Rentenversicherung in Deutschland ist das der 'Teilhabeäquivalenz', das die Proportionalität zwischen Rentenansprüchen und Beitragszahlungen ausdrückt. Verfechter des Systems rechtfertigen dieses Prinzip mit dem Ziel der Verteilungsneutralität. Gerade diese ist jedoch verletzt, weil sich klar definierbare Bevölkerungsgruppen in ihrer Lebenserwartung unterscheiden. – – A basic principle of statutory retirement insurance in Germany is the proportionality between earnings and retirement benefits called 'Teilhabeäquivalenz'. Advocates of the system defend this principle, arguing that it ensures distributive neutrality. However, this assertion is wrong because the principle combines two concepts with different time dimensions: lifetime contributions and monthly retirement benefits. If clearly defined population groups differ in their life expectancy, then this very principle achieves income redistribution, in the German case from low earners to high earners. We propose a simple change in the rules which would avoid this undesirable redistribution.
Keywords: H55; 330; Gesetzliche Rentenversicherung; Verteilungswirkung; Sterblichkeit; Versicherungstechnisches Risiko; Versicherungstechnik; Deutschland